1989
DOI: 10.1016/0014-5793(89)81103-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of free sulfhydryl groups and disulfide bonds in Na+,K+‐ATPase

Abstract: The content of free SH groups and disulfide bonds in the purified pig kidney Na+,K+-ATPase was determined by ammetric titration with silver nitrate. In the native enzyme, most of the free SH groups are masked due to their location in the polypeptide chain regions poorly accessible to SH reagents. Denaturation with 5% SDS and 8 M urea makes these regions accessible thus revealing 22 free SH groups/mol of the protein. After complete blocking of free SH groups with silver ions, 8 SH groups/mol of the protein are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…A decrease in Na + ,K + -ATPase activity was reported in vesicles of rabbit brain choroids plexus [129]. The increase in free –SH group content may imply that phenoxyl herbicides damage the enzyme molecule structure by disruption of disulfide bridges [130]. These disruptions lead to enzyme inactivation.…”
Section: Inhibition Of Na+k+-atpase Activitymentioning
confidence: 99%
“…A decrease in Na + ,K + -ATPase activity was reported in vesicles of rabbit brain choroids plexus [129]. The increase in free –SH group content may imply that phenoxyl herbicides damage the enzyme molecule structure by disruption of disulfide bridges [130]. These disruptions lead to enzyme inactivation.…”
Section: Inhibition Of Na+k+-atpase Activitymentioning
confidence: 99%
“…Similar to most other antigen-antibody interactions, the binding of an antigen is enthalpically driven throughout the physiological temperature range. Structural flexibility of the antigen-antibody site is key to the antigen binding activity [20]. Burgen et al [21] suggested that such a conformational flexibility would result in a faster rate of association and dissociation, a mechanism of recognition tagged the "induced fit" model.…”
Section: Discussionmentioning
confidence: 99%
“…A significant amount of free SH groups in the native globular conformation were masked to attack, due to their location in poorly accessible regions of the folded structure. Therefore, the level of SH groups could be considered as an indication of protein unfolding or denaturation [20].…”
Section: Structural Analysis Datamentioning
confidence: 99%
“…As a consequence, the quantitative measurement of SH groups is a routine task in many applied disciplines where a quick and easy method is much preferred. Electrochemical [3,4] and fluorimetric assays [5,6,7,8] of protein sulfhydryls are very sensitive and accurate but they involve lengthy procedures (complete proteolysis, electrolysis, HPLC separation). Sensitivity and reliability are also good in an enzymatic method where protein sulfhydryls are first reacted with cystamine and the released cysteamine cleaves papain-S-S-CH 3 , yielding active papain-SH which is then assayed with a fluorigenic substrate [9].…”
Section: Introductionmentioning
confidence: 99%